Non-Coding RNA Profiles Of Dengue Virus 1-Infected Aedes albopictus Cells - Azlan,, Azali (2018)
Aedes albopictus (Ae. albopictus), a competent vector of dengue virus (DENV) and Chikungunya virus, is a highly invasive species . It is considered as a public health threat throughout the world because of its high adaptability in both tropical and temperate regions of the world, aggressive spread, and vector competence (Chen et al., 2015). Despite being categorized as less efficient vector of DENV than Aedes aegypti (Ae. aegypti), Ae. albopictus is the principal vector that caused dengue epidemics (Cancrini et al., 2003).